Chinese ideas about nature and society : studies in honour of Derk Bodde - Bodde, Derk, 1909-2003; Le Blanc, Charles; Blader, Susan, 1943- (Hong Kong University Press, 1987)
The main theme that pervades this Festschrift, written by fellow-scholars and students of Bodde for his seventy-fifth birthday, is that of the proper ordering of the universe as it obtains in the Chinese tradition.